JOB SATISFACTION AMONG ACADEMIC STAFF IN HIGHER EDUCATION DURING COVID-19 PANDEMIC: A CONCEPTUAL FRAMEWORK - Nurul Labanihuda Abdull Rahman; Nurul Izzati Idrus (International Journal of Accounting, Finance and Business, 2022)
Job satisfaction is important for employees and organizational outcomes. Work motivation has a positive impact on the performance of employees. The higher the employees’ work motivation, the higher the results of employees’ performances. There is lack of study on the job satisfaction with a combination of Maslow’s Hierarchy of Needs especially during Covid-19 pandemic. Therefore, this study will target on academic staff who have been affected during the Covid-19 pandemic in the northern area. The objective of the study was to find out the relationship between the employees’ motivation factors and job satisfaction. In this study, the independent variables were physiological needs, safety and security needs, self-belonging needs, self-esteem needs, and self-actualization needs, while the dependent variable was job satisfaction. This study was based on Maslow’s Hierarchy of Needs Theory, which indicated the employees’ motivational factors. The result will be analyzed using descriptive analysis to determine the factors of the employees’ motivation that lead to job satisfaction. Moreover, pearson product-moment correlation coefficient also will be used to investigate the relationship between the employees’ motivational factors and job satisfaction. The findings from this study were significant as they helped the organizations’ management to evaluate their employees’ job satisfaction and investigate their employees’ motivation level, whether it was high or low.